Trial of Vaginal Birth After Caesarean (VBAC): Sharing Experience From a Tertiary Care Center of Eastern Nepal - Pokhrel Ghimire, Sita; Ghimire, Ashima; Pokharel, Aruna; Lamichhane, Sabina; Kumar, Mahanand (Journal of Nobel Medical College, 2018)
Background: Rising rates of cesarean section is a matter of great concern and trial of labor in previous cesarean section women is an attractive alternative. Vaginal Birth After Caesarean (VBAC) may be one of the strategy developed to control the rising rate of cesarean deliveries in our country. Analyzing outcome of previous caesarean pregnancies will provide an insight for reducing the caesarean rates and formulating protocols and policies for trial of labor. The purpose of this study is to evaluate the pregnancy outcome in previous caesarean section women with VBAC trial with the hope of avoiding unnecessary repeat caesarean section rates. Methodology: It is a cross-sectional observational institute based study carried out in Nobel Medical College Teaching Hospital from 15th March 2017 to 14th March 2018 after the approval from Institutional Review Committee (IRC). This consists of patient with past history of cesarean section, who delivered in NMCTH during the study period and meeting the Royal College of Obstetrics and Gynecology (RCOG) inclusion criteria for VBAC. Feto-maternal outcomes were analysed. Results: There were 1225 previous cesarean cases, among them, we did VBAC trial in 135(11%) patients, 99 (73.33%) had successful vaginal delivery whereas 36(26.66%) could not do the same after labor trial. Feto-maternal outcome was better in VBAC patients than cesarean group.No maternal and neonatal mortality occurred. Conclusion: In the country like ours where rate of caesarean section is increasing alarmingly we have to try VBAC in appropriate group of patients. National policy and guidelines are necessary after large multicenter prospective studies. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 18-25